If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9u + 5 = 9 Reorder the terms: 5 + 9u = 9 Solving 5 + 9u = 9 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 9u = 9 + -5 Combine like terms: 5 + -5 = 0 0 + 9u = 9 + -5 9u = 9 + -5 Combine like terms: 9 + -5 = 4 9u = 4 Divide each side by '9'. u = 0.4444444444 Simplifying u = 0.4444444444
| 9u= | | -104-8x=7x+16 | | 4x+13=-15-10x | | 150-6x=3x+24 | | 8+5(x-4)=6(x+2) | | -23-5x=7-8x | | 76-5x=7x+16 | | 76-5x=7-8x | | -5n+8(1+7n)=-8 | | 4x+6=78-5x | | 5n+5=2n+14 | | 2+8x=51+x | | 5p-8=15 | | 5d=d+2 | | 3x-5=11x-101 | | 3x+24=13x-66 | | 9x-33=3x+3 | | 4x+71=10x+11 | | .50b+4=.125+88 | | 95-5a=22a+20 | | 4+3(2x+5)=27 | | -31=4x+11-9x-19 | | 5-7a=135-42a | | 0.3k+0.5k+13=1 | | 4.8=0.2(2x+10) | | 2y+4x=8 | | -67-9a=9a+23 | | 6a+11=-19-9a | | 179-6a=6a+23 | | -9-5a=5-7a | | -4(-23)= | | -4x-10=38 |